The Land of Stories : beyond the kingdoms - Colfer, Chris, 1990- (2015)
"The Masked Man possesses a powerful magic potion that turns every book it touches into a portal, and he is recruiting an army of literature's greatest villains! So begins a race through the magical Land of Oz, the fantastical world of Neverland, the madness of Wonderland, and beyond. Can twins Alex and Conner catch up to the Masked Man?"--
Sequel to: The Land of Stories: a Grimm warning.
Keywords: Fairy tales -- Fiction; Characters in literature -- Fiction; Magic -- Fiction; Brothers and sisters -- Fiction; Twins -- Fiction; Youths' writings